Menopausal hormone therapy – from a hypertensiologist’s point of view - Posadzy-Małaczyńska, Anna (Menopause Review/Przegląd Menopauzalny, 2011)
The results of experimental studies and clinical observations from the last two decades indicate the beneficial impact of oestrogens on the cardiovascular system. However, later published large randomized clinical trials (WHI, HERS) did not confirm the benefits of hormonal substitution in primary as well as secondary prevention of cardiovascular diseases in women. Thus it was concluded that the studies should be designed and interpreted in a different way. The reasons for these discrepancies are probably the different effects of oestrogens on the healthy and atherosclerotically changed coronary arteries. We cannot expect that the oestrogens, even in long-term treatment, would reverse the process in an already changed artery wall, which was progressing for years. The time of the start of hormone replacement after the occurrence of menopause may also be significant. The WHI clinical trial, which was by the opponents considered as proof of the lack of benefits of this therapy in primary prevention, concerned a population of women who had been after the menopause for many years.